Enhanced authentication and access control in Internet of Things: a potential blockchain-based method. (24th December 2021) - Muzammal, Syeda Mariam; Murugesan, Raja Kumar
With the rapid growth of Internet of Things (IoT), it can be foreseen that IoT services will be influencing several use-cases. IoT brings along the security and privacy issues that may hinder its wide scale adoption. The scenarios in IoT applications are quite dynamic as compared to the traditional internet. It is vital that only authenticated and authorised users get access to the services provided. Hence, there is a need for a novel authentication and access control technique that is compatible and practically applicable in diverse IoT scenarios to provide adequate security to devices and data communicated. This article aims to highlight the potential of blockchain for enhanced and secured authentication and access control in IoT. The proposed method relies on blockchain technology, which tends to eliminate the limitations of intermediaries for authentication and access control. As compared to existing systems, it has advantages of decentralisation, secured authentication, authorisation, adaptability, and scalability.